2010
DOI: 10.1094/cm-2010-0920-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Weed Control in Dicamba-Resistant Soybeans

Abstract: Field experiments were conducted in 11 states to evaluate broadleaf weed management programs in dicamba‐resistant soybeans which involved the use of preemergence and postemergence dicamba. Preemergence (PRE) dicamba at 0.25 lb ae/acre provided less than 60% control of smooth pigweed, giant ragweed, velvetleaf, palmer amaranth, waterhemp, and morningglory spp., but 97% control of common lambsquarters and horseweed at 3 weeks after treatment (WAT). Preemergence flumioxazin plus chlorimuron or sulfentrazone plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 6 publications
(6 reference statements)
1
67
1
Order By: Relevance
“…In dicamba-tolerant soybean, up to 100% control of GR giant ragweed 8 WAA has been reported from dicamba PP application [19]. On the contrary, reference [20] reported poor control (30%) of GR giant ragweed with dicamba applied PP in dicamba-tolerant soybeans, however, control increased to over 80% when accompanied by a dicamba POST application. Moreover, reference [12] reported that either single or sequential dicamba applications, when timed to appropriately match the biology of the weed species, can be used as an effective integrated weed management tool for the control of GR giant ragweed.…”
Section: Preplant Tank-mixesmentioning
confidence: 99%
See 1 more Smart Citation
“…In dicamba-tolerant soybean, up to 100% control of GR giant ragweed 8 WAA has been reported from dicamba PP application [19]. On the contrary, reference [20] reported poor control (30%) of GR giant ragweed with dicamba applied PP in dicamba-tolerant soybeans, however, control increased to over 80% when accompanied by a dicamba POST application. Moreover, reference [12] reported that either single or sequential dicamba applications, when timed to appropriately match the biology of the weed species, can be used as an effective integrated weed management tool for the control of GR giant ragweed.…”
Section: Preplant Tank-mixesmentioning
confidence: 99%
“…In dicamba-tolerant soybean, up to 100% control of GR giant ragweed has been reported for dicamba applied POST [19] and for sequential early-and late-POST dicamba applications [20]. Up to 90% control of GR giant ragweed has been reported for glufosinate under greenhouse conditions [21]; however, any obstructing vegetation that may be present under field conditions has the potential to decrease control as glufosinate is a contact herbicide and lacks in-plant mobility.…”
Section: Postemergence Tank-mixesmentioning
confidence: 99%
“…(A. trifida L.), and horseweed [Conyza canadensis (L.) Cronquist] (Byker et al 2013;Johnson et al 2010;Spaunhorst and Bradley 2013;Spaunhorst et al 2014;Vink et al 2012). For example, according to Nebraska (93%) and Wisconsin (66%) growers, weed management significantly improved with adoption of dicamba products in soybean (Werle et al 2018).…”
mentioning
confidence: 99%
“…Palmer amaranth control in 2013 in the Dicamba PRE only treatment was 60% at 2 WAP2, whereas, it was only 27% in 2012 at the same rating period. Johnson et al [21] also observed that a PRE only application of dicamba provided < 60% control of Palmer amaranth and morningglory spp. In contrast, the flumioxazin PRE only treatment provided substantially better Palmer amaranth control (>99%) ( Table 4).…”
Section: Palmer Amaranth Controlmentioning
confidence: 97%